Ecolabeling to Improve Product Quality and Reduce Environmental Impact: A Choice Experiment With Vegetable Farmers in Thailand - Praneetvatakul, Suwanna; Vijitsrikamol, Kampanat; Schreinemachers, Pepijn (Frontiers in Sustainable Food Systems, 2022)
The overuse of agricultural pesticides creates high costs to ecosystems and human health. One important reason for overuse is that markets in lower-income countries do not sufficiently differentiate agricultural produce based on quality aspects, making it difficult for consumers to select safe produce. Ecolabeling is a voluntary method of certification to gain consumer trust by differentiating produce based on environmental impact. Most studies have looked at consumer preferences for ecolabels, but the preferences of producers to adopt such labels have received much less attention. This paper aims to explore farmers' choice preference for ecolabels, safe pest management methods, human health, and the environment using a choice experiment. We sampled 303 vegetable farmers from three peri-urban provinces of Bangkok, Thailand, namely Ratchaburi, Nakhon Pathom and Pathum Thani provinces. Attributes of pest management methods and outcomes included farm ecosystems, human health, ecolabels, market opportunities, training in integrated pest management, and additional farm cost. A mixed logit model was employed to quantify the effect of each attribute on farmers' preference and marginal willingness to pay for each attribute. The data show high levels of pesticide use in vegetable production as farmers try to protect their investment from a wide range of pests and diseases. Alternative control methods are not widely available and are used in an ad-hoc manner to complement pesticides rather than substitute them. Farmers' willingness to pay for an ecolabel was 222 US/ha/crop. However, ecolabeling had a lower priority than most other attributes. We conclude that there is a need to promote alternative pest management practices alongside ecolabels to reduce the environmental impact of vegetable farming in peri-urban areas in Thailand.